Management of Completely Edentulous Resorbed Mandibular Ridge with Flabby Tissue Using Suction Method Impression Technique and Lingualized Posterior Occlusal Scheme: A Case Report - Sari, Nila; Rostiny, Rostiny; Dahlan, Agus (Indonesia Prosthodontic Association, 2021)
Background: Oral health problems often leads to edentulism. Post-extraction alveolar ridge will undergo bone resorption and can be aggravated by ill-fitting denture. There are some treatment options for completely edentulous patients. However, conventional complete denture is still one of the most popular treatment options as it is predictable, cost effective, and non-invasive. There are some principles that should be followed to ensure a more comfortable and functional complete denture. Objective: The purpose of this article is to describe how a case of fully edentulous patient, with flabby tissue and flat mandibular ridge, is managed using suction method impression technique and a lingualized posterior occlusal scheme. Case Report: A female patient aged 68 years old came to the Universitas Airlangga Dental Hospital to get a new denture since her previous denture is ill-fitting and unfunctional. The mandibular alveolar ridge is flat and there is flabby tissue in the anterior region of the maxilla and mandible. Case Management: First, a preliminary impression was taken using the reversible hydrocolloid alginate impression material. Then, a bite rim was fabricated from the preliminary model. Next, the horizontal and vertical position of the mandible was determined using the bite rim. The lower bite rim was cut into 4 pillars so that a suction method impression technique could be done. A neutral zone registration was also done for guiding the lower denture teeth arrangement. The posterior occlusal scheme was arranged to be lingualized occlusion. The denture needed some minor adjustment during control. Conclusion: Suction method impression technique combined with lingualized posterior occlusal scheme will make a more retentive and stable complete denture.